2009
DOI: 10.1142/s0219530509001335
|View full text |Cite
|
Sign up to set email alerts
|

Strings, Waves, Drums: Spectra and Inverse Problems

Abstract: This survey treats a number of interconnected topics related in one way or another to the famous paper of Mark Kac, "Can one hear the shape of a drum?": wave motion, classical and quantum inverse problems, integrable systems, and the relations between spectra and geometry. We sketch the history and some of the principal developments from the vibrating string to quantum inverse problems, the KdV equation and integrable systems, spectral geometry and the index problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…Theorem 1.2 shows that the eigenvalues depend on the weights of the Dirac point masses and their positions relative to ν, but that they are independent of the distribution of ν; this condition is different than that given for the Kreȋn-Feller operator ∆ η,Λ , where η is a purely atomic measure, compare with [2].…”
Section: Introduction and Statement Of Main Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Theorem 1.2 shows that the eigenvalues depend on the weights of the Dirac point masses and their positions relative to ν, but that they are independent of the distribution of ν; this condition is different than that given for the Kreȋn-Feller operator ∆ η,Λ , where η is a purely atomic measure, compare with [2].…”
Section: Introduction and Statement Of Main Resultsmentioning
confidence: 96%
“…The problem in two dimensions remained open until 1992, when Gordon, Webb, and Wolpert [12] constructed a pair of regions in the plane that have different shapes but whose associated Laplacians have identical eigenvalues. Nevertheless, as observed by Weyl [30], Berry [3,4], Lapidus et al [21,22,23,24,25], Beals and Greiner [2] and many others, the spectrum of a Laplacian still tells us a lot about the shape of the underlying geometric structure.…”
Section: Introduction and Statement Of Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finding the Hamiltonian operator that generated a given wave-function or rather an effective potential that can generate the wave-function for a quantum system may be related to the famous question made by mathematician Mark Kac [27]: "Can one hear the shape of a drum?" In the case of sound waves, the answer to this question is no for all cases except for the trivial case where the shape of a string is equal to its length [28,29]. In the case of quantum waves, despite the fact that one can get a lot of geometrical and topological information from the spectrum or even its asymptotic behavior, this information is not complete even for quantum systems as simple as the ones defined along a finite interval.…”
Section: Predicting Potentialsmentioning
confidence: 99%
“…The classical Kreȋn-Feller differential operator ∆ ν,Λ , introduced in [8,16], where ν denotes a non-atomic compactly supported Borel probability measure on R and where Λ denotes the one-dimensional Lebesgue measure, has been investigated with respect to its spectral properties first by Fujita [13], Küchler [21], Langer [22] and Kotani and Watanabe [20] and more recently by Arzt [1], Ehnes [6] and Freiberg [9,10,11]. The case when ν is purely atomic has also been studied in [2]; where it was shown that the eigenvalues of ∆ ν,Λ have a dependence not only on the positions of the atoms of ν but also on the weights of the atoms. Returning to the case when ν is a non-atomic, it has been established that ∆ ν,Λ is the infinitesimal generator of a Liouville Brownian motion (also known as gap diffusion, skip-free diffusion, quasi-diffusion or generalised diffusion), see [3,4,7,15,21,22,24,26].…”
Section: Introductionmentioning
confidence: 99%